The missing Eusarcus: generic relocation of Pucrolia minuta, with synonymic notes (Opiliones: Laniatores: Gonyleptidae) - Acosta, Luis E.; Guerrero, Elián L. (Zootaxa, 2021)
The harvestmen family Gonyleptidae (Opiliones), the largest one in the Neotropics (Kury 2003), is astonishingly diverse in eastern South America. The species-rich genus Eusarcus Perty, 1833, is characteristic for this area. It is the second largest gonyleptid genus (Kury 2003; Hara & Pinto-da-Rocha 2010), with a long taxonomical history beginning in the 19th century, when Perty (1833) described the genus together with four species. The number of species increased gradually in the 20th century through the addition of new descriptions and the synonymies of several related genera, with the corresponding species transferals (Hara & Pinto-da-Rocha 2010). Eusarcus is a relatively well-studied taxon that has undergone a thorough systematic revision (Hara & Pinto-da-Rocha 2010). Currently the genus contains 40 valid species, some of them cave-dwellers, with 32 species inhabiting the Atlantic rainforest and Paraná semi-deciduous forests (Saraiva & DaSilva 2016; Santos Júnior et al. 2021). The remaining species are peripheral to the core geographic area and are found in the Brazilian Cerrado, in Paraguay, or in the “Pampas” grasslands of Argentina, Uruguay, and southern Brazil (Hara & Pinto-da-Rocha 2010).